Morphologic study of the internalization of a lysosomal enzyme by the mannose 6-phosphate receptor in cultured Chinese hamster ovary cells. - Willingham, M C (1981)
The binding and internalization of a model lysosomal enzyme, beta-galactosidase, was visualized by use of rabbit anti-beta-galactosidase and goat anti-rabbit IgG; the second antibody was labeled with rhodamine or fluorescein (for detection by fluorescence) or with horseradish peroxidase (for electron microscopy). Chinese hamster ovary cells were incubated with beta-galactosidase at 4 degrees C, and then were washed and sequentially incubated in the cold with the two antibodies. The beta-galactosidase was found primarily in coated pits. The binding of the enzyme was completely inhibited by 5 mM mannose 6-phosphate. After the reaction with enzyme and antibodies, the cells were warmed to 37 degrees C; within 1 minute, the beta-galactosidase--antibody complex had begun to move to uncoated vesicles (receptosomes). After 8 min, the beta-galactosidase--antibody complex was seen in receptosomes near tubular elements in the Golgi/GERL area, within such tubular elements and at times, in vesicular elements that may correspond to coated structures of the GERL system. After 15 min, the enzyme--antibody complex was found in lysosomes near the Golgi/GERL are and a half-hour later it was in lysosomes distributed throughout the cytoplasm. Double-label experiments using beta-galactosidase and gold/alpha 2-macroglobulin showed the presence of the two ligands in the same coated pits and receptosomes. Thus, the pathway for internalization of beta-galactosidase via the mannose 6-phosphate receptor is similar to the pathway established for other ligands such as low density lipoprotein and alpha 2-macroglobulin.